Tinjauan Yuridis tentang Tindak Pidana Penganiayaan Sebagaimana dimaksud dalam Pasal 351 Ayat (1) Kitab Undang-Undang Hukum Pidana: Studi Kasus Putusan No.: 165/Pid.B/2022/Pn.Blt) - Murthado, Akhmad; Pintubatu, D.I Silalahi; GP Magno, Nuno (Jurnal Hukum dan Demokrasi (JHD), 2024)
In general, criminal acts against bodies in the Criminal Code are called "torture". Persecution regulated by the Criminal Code consists of: a. Persecution based on Article 351 of the Criminal Code which is detailed as: Ordinary ill-treatment, Assault which results in serious injury, Persecution which results in the person's death; b. Light maltreatment regulated by Article 352 of the Criminal Code; c. Premeditated maltreatment regulated by Article 353 of the Criminal Code with the following details: Causing serious injuries, resulting in the death of the person; d. Serious maltreatment regulated by Article 354 of the Criminal Code with the following details: resulting in serious injuries, resulting in the death of the person; e. Serious and premeditated ill-treatment is regulated by Article 355 of the Criminal Code with the following details: Serious and premeditated ill-treatment Serious and premeditated ill-treatment that results in the person's death. The main problem in writing this thesis is what is the basis for the formulation of Article 351 of the Criminal Code as a criminal act of abuse and whether the Panel of Judges correctly considered it in case No.165/Pid.B/2022/PN.Blt. The research method used is normative juridical research, namely by collecting and studying books related to the issues discussed. The authors' conclusions 1) that the basis for the formulation of Article 351 of the Criminal Code is a criminal act of persecution, namely intentionally causing bad feelings (suffering), pain (pijn), or injury. From the facts revealed at the trial, the defendant had assaulted FEBRIANTI RETNO REJEKI and the victim received injuries as a result of post mortem et repertum from the Syuhada Haji Hospital Number 281/RSSH/IV/2022 dated 23 April 2022 and this caused temporary obstacles in carrying out his activities. time; 2) that the consideration of the Panel of Judges in criminal case No. 165/Pid.B/2022/PN.Blt which stated that the defendant's actions were a criminal act of persecution, because based on the facts revealed at trial, all the elements of a criminal act of persecution were indeed fulfilled. Therefore, it is appropriate for the judges' decision to impose a sentence on the defendant. The author's suggestions 1) that if all the elements indicted have been met, it would be better for the panel of judges to decide more than half of the demands of the public prosecutor; 2) The panel of judges must be more careful in providing legal considerations so that the decisions handed down achieve a sense of justice for all parties.